Analysis of the Influence of Online Consumer Reviews, Perceived Quality, and Price Perception on Purchase Decisions at the Charles and Keith Brand in Semarang - Shulcha, Ficryna -; Karnowahadi, Karnowahadi -; Subandi, Subandi - (Admisi dan Bisnis, 2024)
The research focuses on Charles and Keith customers in Semarang, with data collected from 869 customers who registered for membership in 2023. Purposive sampling technique was employed to gather 150 respondents for the study. The study utilizes Online Consumer Review (X1), Perceived Quality (X2), and Price Perception (X3) as independent variables, while Purchase Decision (Y) serves as the dependent variable. It employs a quantitative approach using literature review and questionnaires for data collection, with Likert scale employed for measurement. Data analysis was conducted using SPSS Version 29. The regression equation obtained is Y = 12.221 + 0.044Online Consumer Review + 0.239Perceived Quality + 0.077Price Perception. The results indicate that Online Consumer Review, Perceived Quality, and Price Perception collectively have a significant and positive influence on Purchase Decision. However, only Perceived Quality significantly and positively influences Purchase Decision